2005
DOI: 10.1108/14676370510573131
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of attitudes of pedagogical students towards environmental education in Greece

Abstract: PurposeGreek pedagogical students’ attitudes towards environmental education in Greece are very important as these students represent future teachers who will affect the success of environmental education in schools. Therefore, the identification of their views will give us the potentiality to modify the curricula of pedagogical departments accordingly.Design/methodology/approachThe use of a questionnaire was chosen as the most suitable method to review and record pedagogical students’ attitudes towards enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 5 publications
2
20
0
1
Order By: Relevance
“…This fact confirms the Sociology of Education hypothesis for the association of economic inequalities with school dropout (Kyridis, 1998, Kyridis et al 2011a). Also the other reasons which led to early school leaving (family and personal) array with the classic causes of dropouts.…”
Section: Journal Of Sociological Researchsupporting
confidence: 80%
See 1 more Smart Citation
“…This fact confirms the Sociology of Education hypothesis for the association of economic inequalities with school dropout (Kyridis, 1998, Kyridis et al 2011a). Also the other reasons which led to early school leaving (family and personal) array with the classic causes of dropouts.…”
Section: Journal Of Sociological Researchsupporting
confidence: 80%
“…And it's really interesting that these regions have low educational development indicators even when at the same time are areas with high rates of economic growth. Decades of research have shown that these same areas had always lower rates of educational development either in reference to individual indicators or to separate indicators combined (Kyridis et al 1995;Kyridis et al 1998;Kyridis et al 1999a;Kyridis et al 1999b;Kyridis et al 1999c;Kyridis & Drossos, 2001;Kyridis, 1997. It is a fact that allows another explanation for the high concentration of Neets in the regions mentioned above.…”
Section: The Greek State Of Affairs With Regard To Neetsmentioning
confidence: 99%
“…However, despite this limited knowledge, some research suggests that student teachers have positive attitudes towards EE. Kyridis, Mavrikaki, Tsakiridou, Daikopoulos and Zigouri (2005) administered a questionnaire that assessed attitudes towards EE of 76 primary school student teachers and 96 kindergarten student teachers after completion of a six-month EE course. The dimensions of analysis covered: the methodology used in EE; the role of EE in the curriculum; objectives and issues addressed by EE and the relationship between students and EE.…”
Section: Evaluation Of Ee In Pspttmentioning
confidence: 99%
“…It is used Holland's methodology to develop a questionnaire with 42 Likert-type questions, grouped in seven to six clusters according to Holland's vocational types [3]. Each group includes questions of vocational interest and one or two of environmental interest.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental attitudes are conceptualized in terms of behavioral theory as being composed of beliefs towards an object [3]. The environment as an object is difficult to define; it may be an attitude object which has been forced on the respondent by journalists and researchers, but it may not make sense to respondents who see the environment much more in terms of its component parts that they personally experience.…”
Section: Introduction mentioning
confidence: 99%